Members of Venezuelan Equine Encephalitis complex entry into host cells by clathrin-mediated endocytosis in a pH-dependent manner - Ghietto, Lucía María (2022)
Pixuna virus (PIXV) and Río Negro virus (RNV) are mosquito-borne alphaviruses belonging to the Venezuelan Equine Encephalitis (VEE) complex, which includes pathogenic epizootic and enzootic subtypes responsible for life-threatening diseases in equines. Considering that the first steps in viral infection are crucial for the efficient production of new progeny, the aim of this study was to elucidate the early events of the replication cycle of these two viruses. To this end, we used chemical inhibitors and the expression of dominant-negative constructs to study the dependence of clathrin and endosomal pH on PIXV and RNV internalization mechanisms. We demonstrated that both viruses are internalized primarily via clathrin-mediated endocytosis, where the low pH in endosomes is crucial for viral replication. Contributing knowledge regarding the entry route of VEE complex members is important to understand the pathogenesis of these viruses and also to develop new antiviral strategies.